High-Stability and Fast Calibration-Free Temperature Measurement Based on Light-Induced Thermoelastic Spectroscopy - Xiaonan Liu; Shunda Qiao; Ying He; Yufei Ma (Ultrafast Science)
In this paper, a series of calibration-free temperature measurement methods based on light-induced thermoelastic spectroscopy (LITES) are proposed for the first time. These techniques utilize the steady-state and transient response characteristics of the quartz tuning fork (QTF), namely, the calibration-free LITES (CF-LITES) and calibration-free heterodyne LITES (CF-H-LITES) methods. Four methods, first harmonic (1f) difference signal to normalize the second harmonic (2f) fundamental signal (method I, 2ffund/1fdiff), 1f overtone signal to normalize the 2f fundamental signal (method II, 2ffund/1fover), 1f heterodyne difference signal to normalize the 2f heterodyne fundamental signal (method III, 2f-Hfund/1f-Hdiff), and 1f heterodyne overtone signal to normalize the 2f heterodyne fundamental signal (method IV, 2f-Hfund/1f-Hover), for simultaneously detecting 1f and 2f within the frequency response range of the QTF are proposed to achieve calibration-free measurement. A self-designed T-shaped QTF with low fundamental and overtone frequencies was used to increase the energy accumulation time, thereby enhancing the sensor signal level. A 3-stage tube furnace was adopted to verify the performance of these 4 methods. Experimental results showed that the errors for the 4 methods were less than 4%, with a standard deviation below 11 °C. Furthermore, the calibration-free method, which employs normalization of the 2f signal with the 1f signal, effectively mitigates the impact of laser beam jitter and power fluctuations on detection performance. A superior performance can be obtained by adopting the CF-H-LITES technique based on method IV. It not only has excellent detection performance but also reduces the measurement period to 4 s, which is about 5 times faster. This development shows substantial promise for expanding the application of the CF-LITES and CF-H-LITES techniques in harsh environments.